Normal functors in the coarse category - Frider, V. (Algebra and Discrete Mathematics, 2005)
We define the canonical coarse structure on the
spaces of the form FX, where F is a finitary normal functor of
finite degree and show that every finitary (i.e., preserving the class
of finite spaces) normal functor of finite degree in Comp has its
counterpart in the coarse category.